Diagnóstico de los riesgos del uso de internet de la guía del Ministerio de Educación del Ecuador para prevención de riesgos durante el uso de internet y dispositivos tecnológicos en el tercer año de bachillerato general unificado de la Unidad Educativa Fiscomisional La Inmaculada en el año lectivo 2022 – 2023. - Vargas Barragán, Pablo Gabriel (2024)
The present research seeks to diagnose the risks of internet use of the Ministry of Education of Ecuador guide for the prevention of risks during the use of internet and technological devices in the third year of unified general high school of the Fiscomisional Educational Unit La Inmaculada in the school year 2022 - 2023, for which an Ad hoc structured questionnaire was developed and adapted as of the guide for the prevention of risks during the use of internet and technological devices of the Ministry of Education of Ecuador (2020), distributed by dimensions, applied in person, through the survey technique, whose meter corresponds to the Likert frequency scale and dichotomous questions of Yes and No, the results showed that the educational institution has occasionally provided information on: human trafficking, grooming, child pornography, sexting, stalking, impersonation and digital media crimes, while flamming, hacking, harassment, phishing, sextortion and lolicon/shotacon have never been addressed. The methodology was carried out by applying the deductive method with a quantitative approach and a descriptive exploratory research design, according to article 216 of the Academic Regulations of the Loja National University. Keywords: Internet risks, Ministry of Education guide in Ecuador.